How Organizational Management Affect Employees’ Motivation and Service Quality: A Study of Kentucky Fried Chicken (KFC) - Nor Husna; Daisy Mui Hung Kee; Nur Wadhihah Amirah; Rusyda Syazreeza; Nur Alissa Fatihah; Shweta Pandey; Shreyas Agnihotri; Rudresh Pandey (International Journal of Applied Business and International Management, 2020)
This study aims to determine how organizational management affects organization’s employees, their motivation and service quality they deliver to the customers. This research was conducted on a world-famous Restaurant Chain - Kentucky Fried Chicken. KFC is a subsidiary of Yum! Brands, the world’s most popular chicken restaurant chain. KFC has been serving Finger Lickin’ Good Chicken since 1930 and has settled itself in 118 countries all over the world with a total of 18,875 restaurants. KFC is recognized for its high customer satisfaction. It is proven that how management treats their workers can affect their worker’s motivation and company’s service quality. A positive attitude of management towards workers might result in higher motivation which contributes to greater performance along with high quality of service. The study comprises of both primary and secondary data to obtain the relevant information & findings.